Tyrosine Phosphorylation of NR2B Contributes to Chronic Migraines via Increased Expression of CGRP in Rats. (14th March 2017) - Liang, Xiping; Wang, Sha; Qin, Guangcheng; Xie, Jingmei; Tan, Ge; Zhou, Jiying; McBride, Devin W.; Chen, Lixue
Abstract : Tyrosine phosphorylation of NR2B (NR2B-pTyr), a subunit of the N-methyl-D-aspartate (NMDA) receptor, has been reported to develop central sensitization and persistent pain in the spine, but its effect in chronic migraines has not been examined. We hypothesized that tyrosine phosphorylation of NR2B contributes to chronic migraines (CM) through calcitonin gene-related peptide (CGRP) in rats. Ninety-four male Sprague-Dawley rats were subjected to seven inflammatory soup (IS) injections. In a subset of animals, the time course and location of NR2B tyrosine phosphorylation were detected by western blot and immunofluorescence double staining. Another set of animals were given either genistein, vehicle, or genistein and recombinant CGRP. The mechanical threshold was measured, the expressions of NR2B-pTyr, NR2B, and CGRP were quantified using western blot, and nitric oxide (NO) was measured with the nitric acid reductase method. NR2B-pTyr expression, in neurons, peaked at 24 hours after CM. Genistein improved the mechanical threshold and reduced migraine attacks 24 and 72 hours after CM. Tyrosine phosphorylation of NR2B decreased the mechanical threshold and increased migraine attacks via upregulated CGRP expression in the rat model of CM. Thus, tyrosine phosphorylation of NR2B may be a potential therapeutic target for treatment of CM.